2021
DOI: 10.3390/nano11051151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Impacts of Dietary Exposure to Nanoplastics Combined or Not with Arsenic in the Caribbean Mangrove Oysters (Isognomon alatus)

Abstract: Nanoplastics (NPs) are anthropogenic contaminants that raise concern, as they cross biological barriers. Metals’ adsorption on NPs’ surface also carries ecotoxicological risks to aquatic organisms. This study focuses on the impacts of three distinct NPs on the Caribbean oyster Isognomon alatus through dietary exposure. As such, marine microalgae Tisochrysis lutea were exposed to environmentally weathered mixed NPs from Guadeloupe (NPG), crushed pristine polystyrene nanoparticles (PSC), and carboxylated polysty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 108 publications
(162 reference statements)
1
14
1
Order By: Relevance
“…This could underline a disturbance of the energetic balance leading to an oxidative stress in clams after NP-L entry. Similar trends were observed in previous studies on the pacific oyster I. alatus exposed through the direct route to NPs, with the up-regulation of cav, 12S and cat genes 33 , whereas it was not observed after dietary exposure 15 . Surprisingly, no response was observed towards apoptosis in gills, with a global inhibition of gadd45, p53 and bax in all conditions tested (except Al).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This could underline a disturbance of the energetic balance leading to an oxidative stress in clams after NP-L entry. Similar trends were observed in previous studies on the pacific oyster I. alatus exposed through the direct route to NPs, with the up-regulation of cav, 12S and cat genes 33 , whereas it was not observed after dietary exposure 15 . Surprisingly, no response was observed towards apoptosis in gills, with a global inhibition of gadd45, p53 and bax in all conditions tested (except Al).…”
Section: Discussionsupporting
confidence: 90%
“…These results are quite different from other studies made under marine conditions on the pacific oysters. The expression of cox1 in gills of Isognomon alatus was not modulated after neither water- nor diet borne exposures to environmental NPs for 7 days 15 , 31 . However, the expression of 12s was up-regulated in gills of I. alatus after direct exposure to environmental NPs 31, 33 while it was down-regulated in the present study.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The authors showed that these environmentally relevant NPs could impact algae and bivalves by inhibiting the cell growth of Scenedesmus subspicatus and incrementing the fecal and pseudofecal production of Corbicula fluminea (Baudrimont et al, 2020). Another study on mangrove oysters Isognomon alatus demonstrated that dietary exposure to nanoplastics (10-100 µg/L) produced from microplastics collected on Caribbean beaches could modulate genes involved in oxidative stress (up-regulation of the catalase gene) (Lebordais et al, 2021). Moreover, a recent study on Isognomon alatus demonstrated the synergic effect of arsenic (1 mg/L), when combined to NP exposures (7.5 to 15 µg/L) on response against oxidative stress (up-regulation of cat) and apoptosis (up-regulation of bax and p53 genes) (Arini et al, 2022).…”
Section: Introductionmentioning
confidence: 99%